Analysis of the sustained virological response in patients with chronic hepatitis C and liver steatosis - Piccoli,Leonora De Zorzi (2011)
CONTEXT: Chronic hepatitis C as well as non-alcoholic fatty liver disease are recognized as the main cause of liver disease in Western countries. It is common to see the concomitance of the diseases and the influence of steatosis in the sustained virological response of patients with hepatitis C virus. OBJECTIVE: Assess the sustained virological response in chronic hepatitis C patients according to the presence of liver steatosis. METHODS: One hundred sixty patients with chronic hepatitis C were retrospectively evaluated. Demographic data such as gender, age, body mass index, presence of diabetes mellitus and systemic arterial hypertension, virus genotype and use of pegylated interferon were analyzed, as was the staging of fibrosis and the presence of steatosis at histology. RESULTS: Most patients were male (57.5%), with a mean age of 48 ± 9.7 years. The most frequent genotype observed was 3 (56.9%) and, in the histological evaluation, steatosis was observed in 65% of the patients (104/160). Sustained virological response in patients with steatosis occurred in 38.5%, and in 32.1% in patients without steatosis (P = 0.54). When we analyzed possible factors associated with the presence of steatosis, only body mass index and systemic arterial hypertension revealed a significant association. When the factors that influenced sustained virological response were evaluated in a logistic regression, genotype and use of pegylated interferon proved to be independent factors associated to the response. CONCLUSION: In the evaluated patients the presence of liver steatosis did not influence the sustained virological response of patients with chronic hepatitis C treated with interferon and ribavirin.